The Application of YouTube Media in Learning Speaking: Students’ Perceptions - Puput Ariyanti; Tri Wintolo Apoko (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
English has an important role as a global language, especially in the era of globalization. To master English, there are four types of proficiency skills such as listening, speaking, reading, and writing. Speaking is the simplest form of communication in life. However, the teaching techniques in Indonesia used by teachers are generally unattractive and monotonous. Students are only provided with textbooks and conventional materials; therefore, it affects students' opportunities to improve their speaking skills. This study aimed to determine students' perceptions of YouTube as a learning media to improve English-speaking skills. This study used a mixed method which cover quantitative and qualitative designs. Thus, the instruments include the questionnaires distributed via Google Form to 215 of the 11th grade students of State Senior High School No. 58 Jakarta and interview for selected students. The result showed that there were five aspects of student perceptions such as: convenience, motivation, progress, activity, and variation. The largest percentage value was obtained by variation aspect in positive perception of 58.37%. The students' perception of YouTube as a learning media was then positive. In addition, YouTube had a positive impact by proving students’ progress in English-speaking skills.